Association Between Diurnal Temperature Range and Risk of Cardiomyopathy-Induced Hospitalisation in Henan, China: A Time-Series Study - Zhang Z; Wang Y; Zhou Y; Pei J; Zhao G; Dong P; Yang K; Liu H; Xie N; Li X; Zang X; Lin F; et al. (Risk Management and Healthcare Policy)
Zhaolin Zhang,1,* Yongbin Wang,2,* Yifeng Zhou,1 Jiachao Pei,1 Guoan Zhao,1,3 Pingshuan Dong,4 Kan Yang,5 Hui Liu,6 Na Xie,7 Xuefang Li,3 Xiayan Zang,3 Fei Lin,1,3 Zhigang Chen1 1Department of Cardiology,The First Affiliated Hospital of Xinxiang Medical University, Weihui, 453100, People’s Republic of China; 2Department of Epidemiology and Health Statistics, Xinxiang Medical University, Xinxiang, 453003, People’s Republic of China; 3Henan Engineering Technology Research Center of Environmental Meteorological Medicine, The First Affiliated Hospital of Xinxiang Medical University, Weihui, 453100, People’s Republic of China; 4Department of Cardiology,The First Affiliated Hospital of Henan University of Science and Technology, Luoyan, 471000, People’s Republic of China; 5Department of Cardiology,Nanyang Central Hospital, Nanyang, 473005, People’s Republic of China; 6Department of Cardiology,Anyang District Hospital, Anyang, 455000, People’s Republic of China; 7Department of Cardiology,The Third Affiliated Hospital of Xinxiang Medical University, Xinxiang, 453003, People’s Republic of China*These authors contributed equally to this workCorrespondence: Fei Lin; Zhigang Chen, Department of Cardiology,The First Affiliated Hospital of Xinxiang Medical University, No. 88 Jiankang Road, Weihui, Henan, People’s Republic of China, Tel +86 18567557937, Email 1fy2000129@xxmu.edu.cn; 1fy2015157@xxmu.edu.cnPurpose: The effect of the diurnal temperature range (DTR) on human health in diverse geographic areas and the potential confounding factors are not fully understood. Additionally, while a robust association has been reported between temperature and cardiomyopathy (CM), evidence of the impact of DTR is relatively limited. Here, we determined whether an association exists between DTR and CM hospitalisations in vulnerable populations.Methods: CM admission data (2016– 2021) were collected from seven tertiary hospitals in Henan.We used a GAM combined with a distributed lag non-linear model (DLNM) to investigate the delayed effects of DTR on daily hospitalisations for CM.Stratified analysis was performed in subgroups according to sex, age, and season. Attributable fractions (AF) and attributable numbers (AN) were employed to illustrate the disease burden and investigate the association between temperature and DTR.Results: Overall, 5,757 CM cases were identified. DTR and CM admissions exhibited a non-linear correlation. High DTR (P95: 15.5 °C) and low DTR (P05: 3 °C) increased CM admission risk, with low DTR having a stronger effect. Males and warm seasons were significantly more susceptible to DTR, and low DTR affected youth and adults more than older adults. AF and AN of low DTR on CM admissions were 51% and 2,936, respectively.Conclusion: Our results revealed a significant association between DTR and CM hospitalisations, providing valuable insights for the development targeted prevention and control measures.Keywords: cardiomyopathy, diurnal temperature range, distributed lag non-linear model, time-series